PENGGUNAAN BAHASA INDONESIA PADA DISKUSI SISWA SMANEGERI 4 SURAKARTA : KAJIAN DENGAN PRINSIP KERJA SAMA GRICE DAN RELEVANSINYA SEBAGAI BAHAN AJAR KETERAMPILAN BERBICARA - B A M, Sarah Apriani; Setiawan, Budhi; Saddhono, Kundharu (Universitas Sebelas Maret, 2018)
This study aims to (1) describe and explain the realization of the following Grice’s cooperative principles; (2) describe and explain the realization of the violatting Grice’s cooperative principles; and (3) explains the relevance of Grice's principles of cooperation as teaching materials for high school speaking skills. This research is a qualitative descriptive research. Sources of data was a transcripted document form. The technique for taking the subject was done by purposive sampling. Data analysis in this study was using the flow model. The results of the study are as follows. First, the maxim of ’quantity’ of the Grice’s cooperative principle of was the most followed as many as 35 data (59,3%). Second, the maxim of ‘quantity’ was also the most violated as many as 33 data (48,5%). Third, Grice’s coopertive principles can be used as teaching materials of speaking skills in high school because (1) it provides guidance to students; (2) it provides guidance for teachers in giving score; and (3) it improves effectiveness in the learning process of speaking skills, especially in discussion activities.